Hey!
Alright, the first step to solving this division problem would be to convert the mixed fraction into a simple fraction. To do that, we'll multiply the denominator by the whole number and then add that total to the numerator.
<em>Original Fraction :</em>
![3 \frac{3}{4}](https://tex.z-dn.net/?f=3%20%5Cfrac%7B3%7D%7B4%7D%20)
<em>New Fraction {Changed by Conversion} :</em>
![\frac{15}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B15%7D%7B4%7D%20)
Now that we've successfully done that we'll have to change the equation.
<em>Old Equation :</em>
![\frac{15}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B15%7D%7B4%7D%20)
÷
![\frac{2}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B8%7D%20)
= ?
<em>New Equation {Changed by Flipping the Second Fraction and the Symbol} :</em>
![\frac{15}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B15%7D%7B4%7D%20)
·
![\frac{8}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B8%7D%7B2%7D%20)
= ?
Now we multiply straight across.
<em>Old Equation :</em>
![\frac{15}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B15%7D%7B4%7D%20)
·
![\frac{8}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B8%7D%7B2%7D%20)
= ?
<em>Solved :</em>
![\frac{120}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B120%7D%7B8%7D%20)
Almost done!
Now we have to simplify the fraction.
<em>Old Fraction :</em>
![\frac{120}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B120%7D%7B8%7D%20)
<em>New Fraction {Changed by Simplification} :</em>
![\frac{15}{1}](https://tex.z-dn.net/?f=%20%5Cfrac%7B15%7D%7B1%7D%20)
Now just convert it to a whole number by removing the fraction line and the number, and that's it!
<span><em>So,
![3 \frac{3}{4}](https://tex.z-dn.net/?f=3%20%20%5Cfrac%7B3%7D%7B4%7D%20)
÷
![\frac{2}{8}](https://tex.z-dn.net/?f=%20%5Cfrac%7B2%7D%7B8%7D%20)
equals</em></span>
15.
Hope this helps!
- Lindsey Frazier ♥
Don't know if this helps but the small thing will fit in the big shape about 6 times
<span />
I believe you are correct keep it up
18/24 can both be divided by 6, so it's 3/4
Answer: y=-3x/4 -1/4
Step-by-step explanation:
y=mx+b
-1=-3/4 * 1 +b
-1=-3/4 + b
(-1=-3/4 + b)*4
-4=-3+4b
4b=-1
b=-1/4
y=-3x/4 -1/4